Achievement of guideline recommended LDL-C goals in patients with acute myocardial infarction (AMI) in Switzerland. (14th October 2021) - Hoepli, A; Ahmed, K; Rickli, H; Eberli, F; Kobza, R; Pedrazzini, G; Radovanovic, D
Abstract: Background: In 2016 and subsequently again in 2019 the ESC/EAS Guidelines for the Management of Dyslipidaemia established a more intensive reduction of LDL cholesterol (LDL-C) treatment recommendations. We aim to characterize patients with acute myocardial infarction (AMI) with regards to achievement of recommended LDL-C goals and their current lipid lowering therapy. Methods: We retrospectively analysed patients with AMI admitted to Swiss hospitals between 2016 and 2020. Patients were classified as "very high risk" due to prior atherosclerotic cardiovascular disease (ACSVD) events including at least one of the following: Myocardial infarction (MI), stroke, peripheral arterial disease (PAD) and type 2 diabetes mellitus with target organ damage. The remaining patients were classified as "other risk". LDL-C treatment recommendation goals for the "very high risk" population were set to 1.8mmol/L (2016 ESC/EAS Guidelines) or 1.4mmol/L (2019 ESC/EAS Guidelines) and for the "other risk" population to 2.6mmol/L or 1.8mmol/L. To identify differences between the two groups the Mann-Whitney test was used and for differences within a group the Kruskal-Wallis test. In-hospital outcomes were summarised as major adverse cardiac and cerebrovascular events (MACCE). Results: Among 7114 patients included, 18.4% were categorized as "very high risk" and 81.6% as "other risk" (p<0.001). In general, the "very high risk" patients were older (69.2y vs. 63.6y, p<0.001), more likely to be men (78.8% vs. 75.3%, p=0.007), had poorer in-hospital outcomes (6.0% vs. 3.4%, p<0.001) and were more often on lipid lowering treatment (statin/ezetimibe/combination) (LLT) prior to admission (64.8% vs 14.0%, p<0.001). The overall LDL-C median for the "very high risk" population was significantly lower than for the "other risk" population (2.4mmol/L vs. 3.5mmol/L, p<0.001). In addition, median (IQR) LDL-C increased in the "other risk" group over the years from 3.5mmol/L (2.7; 4.2) in 2016 to 3.7mmol/L (3.1; 4.4) in 2020. In contrast, no change in LDL-C was observed in the patients at higher risk (Fig. 1). Patients in the "other risk" group were more likely to miss the recommended LDL-C goals (2016 Guidelines: 80.0% vs. 75.4%, 2019 Guidelines: 94.2% vs. 89.1%). Patients without LLT prior to admission had a higher chance of not reaching the recommendations compared to patients with LLT prior to admission (without LLT: 2016: 85.3% vs. 91.0%, 2019: 96.1% vs. 96.6%), (with LLT: 2016: 50.8% vs. 66.8%, 2019: 83.2% vs.85.2%) (Fig. 2). Conclusion: Median LDL-C levels have tended to increase in recent years in patients with very high CV risk and AMI admitted to Swiss hospitals. Despite existing lipid lowering therapies only few patients met guideline recommended LDL-C goals. Our results indicate that clinical implementation of guidelines remains to be optimised with regards to achievement of LDL-C goals to reduce CV risk and improve outcomes. Funding Acknowledgement: Type of funding sources: None.